Seed health and quality of some selected rice varieties and their management - Akter, Mst Arjina; Dey, Purnima; Sultana, Fahmida; Hossain, Ismail (Asian-Australasian Journal of Bioscience and Biotechnology, 2017)
A study was conducted for assessing seed health status of four varieties of rice (Oryza sativa) viz. BR 11, BRRI Dhan 28, BRRI Dhan 29 and BRRI Dhan 40 and management of seed borne fungal pathogens by selected chemical namely Thiovit (4%) and a bio-control agent BAU-Biofungicide @ 2% (Trichoderma based preparation) at Seed Pathology Center (SPC) and M.S. Laboratory, Department of Plant Pathology, Bangladesh Agricultural University (BAU), Mymensingh. Seed health test by blotter method revealed that seven seed borne fungi belonging to six genera viz. Alternaria padwickii (0.5%-1%), Bipolaris oryzae (1%-6.5%), Curvularia lunata (1%-5.5%), Fusarium moniliforme (3%-8.5%), Fusarium oxysporum (2%-9%), Aspergillus flavus (0.5%-1.5%) and Penicillium spp (0.5%-1%) were associated with the seeds. Germination of seeds of the four selected rice varieties varied from 94% to 98.50% (blotter method). In treated seeds, germination ranged from 88-100%. The highest germination (100%) was found in BRRI Dhan 28 when seeds were treated with BAU-Biofungicide and the lowest was (88%) in BRRI Dhan 29. The tested samples produced healthy seedlings (77 to 98%), diseased seedlings (2 to 15%), diseased seeds (0 to 7%) and dead seeds (0 to 5%). Upto 18.18% higher formation of healthy seedlings over control was achieved by treating seeds with BAU-Biofungicide and it also significantly decreased (upto 81.82%) formation of diseased seedlings over the control treatment. The highest vigor index (1306%) was in BRRI Dhan 28 when seeds were treated with BAU-Biofungicide and the lowest was (2805%) in BRRI Dhan 29 under control (untreated). Moreover, BAU-Biofungicide increased up to 81.82% Vigor index over untreated control. Asian Australas. J. Biosci. Biotechnol. 2017, 2 (1), 75-80